2017
DOI: 10.3847/1538-4357/aa83ba
|View full text |Cite|
|
Sign up to set email alerts
|

Formation and Reconnection of Three-dimensional Current Sheets with a Guide Field in the Solar Corona

Abstract: We analyze a series of three-dimensional magnetohydrodynamic numerical simulations of magnetic reconnection in a model solar corona to study the effect of the guide field component on quasi-steady state interchange reconnection in a pseudostreamer arcade configuration. This work extends the analysis of Edmondson et al. (2010b) by quantifying the mass density enhancement coherency scale in the current sheet associated with magnetic island formation during the nonlinear phase of plasmoid-unstable reconnection. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 102 publications
(128 reference statements)
3
19
0
Order By: Relevance
“…Our prior analysis of 27 jets in an equatorial coronal hole found no direct correlation between emerging flux and the observed activity: the bright point sources emerged hours to days before any jets were generated (Kumar et al 2019). Our present observations reveal that plasmoids form in the 3D BCS, which is consistent with recent high-resolution 3D MHD simulations of breakout reconnection (Edmondson et al 2010;Wyper & Pontin 2014a,b;Edmondson & Lynch 2017). Our new observations imply that, in fact, plasmoids are a central feature of all fast reconnection.…”
Section: Discussionsupporting
confidence: 92%
“…Our prior analysis of 27 jets in an equatorial coronal hole found no direct correlation between emerging flux and the observed activity: the bright point sources emerged hours to days before any jets were generated (Kumar et al 2019). Our present observations reveal that plasmoids form in the 3D BCS, which is consistent with recent high-resolution 3D MHD simulations of breakout reconnection (Edmondson et al 2010;Wyper & Pontin 2014a,b;Edmondson & Lynch 2017). Our new observations imply that, in fact, plasmoids are a central feature of all fast reconnection.…”
Section: Discussionsupporting
confidence: 92%
“…The guide field has recently been shown to control both the efficiency of particle acceleration by the Fermi mechanism in plasmoids (Dahlin et al 2016;Arnold et al 2021) and the internal structure of the plasmoids themselves. For example, Edmondson & Lynch (2017) found that the correlation length of magnetic fluctuations along the guide-field direction increases with the guide-field ratio.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The formation and instability of current sheets with stretched magnetic field lines is a common problem in both magnetotail and solar physics (Reeves et al., 2008; Terasawa et al., 2000). In the latter case magnetic reconnection is believed to explain charged particle acceleration and magnetic field energy release in eruptive flares (the so called standard CSHKP model, see Carmichael, 1964; Hirayama, 1974; Kopp & Pneuman, 1976; Sturrock, 1966), non‐eruptive events (including, e.g., coalescence of magnetic loops, see Sakai & de Jager, 1996), streamers (e.g., Edmondson & Lynch, 2017; Riley & Luhmann, 2012; Réville et al., 2020), and solar wind current sheets (Gosling, 2012; Phan et al., 2006). In contrast to the magnetotail investigations, mostly focused on the stabilization of the tearing mode by Bz field, the theory of tearing instability for solar applications is dominated by models of resistive tearing mode in Bz=0 sheets (e.g., Del Sarto et al., 2016; Dobrowolny et al., 1983; Loureiro et al., 2012; Ofman et al., 1991; Tenerani et al., 2015).…”
Section: Introductionmentioning
confidence: 99%